Depressive Symptoms among Patients in Primary Care Centers: Cross-Section Study - Rasool, Ola Badri; Salam Fasal Lafta; Zainab Mohmmad Jawad Hasan (Karbala Journal of Medicine, 2025)
Background: Depression is a common mental health condition that often presents with physical or somatic symptoms in primary care settings. The aim of this study is to investigate the prevalence of depressive symptoms among patients presenting with somatic complaints in a primary care setting Methods: A cross-sectional study was conducted with 106 adult patients presenting to a primary care clinic with somatic complaints. Participants completed self-report measures of depression and somatic symptoms. Depressive symptoms were assessed using a self-report scale based on the criteria of the Diagnostic and Statistical Manual of Mental Disorders (PHQ-9). Results: The age group 38-47 had the highest proportion of participants, while a smaller proportion of individuals were aged 18-27 years (N = 12, 11.3%). The gender distribution was shown as 45.3% males and 54.7% females. After investigating the prevalence of depression among participants and examining the potential demographic factors that were associated, results showed a significant 65% experienced some level of depression. Marital status emerged as an important predictor of depression. Married individuals were less likely to experience depression compared to those who were single, divorced, or widowed. On the other hand, age, sex, number of children, and income level were not found to be significant predictors of depression. Conclusions: The prevalence among primary care patients presenting with somatic complaints. Screening for depression and providing integrated care for both mental and physical health concerns are important in this patient population. Further research is needed to develop and test interventions to improve patient outcomes. Keywords: depression, primary care, somatic symptoms, integrated care.